Solitary multicystic lesion lung cancer: two case reports and review of the literature - Xi Tang (BMC, 2021)
Abstract Background Lung cancer associated with cystic airspaces, especially solitary multicystic lesion lung cancer, is a rare disease (a rare imaging performance of non-small cell lung cancer). It is difficult to diagnose owing to the lack of a clear definition; therefore, diagnosis of these neoplastic lesions remains challenging. Case presentation We outlined two cases of elderly Chinese men who were admitted to the hospital with a solitary multicystic lesion of the lung and subsequent surgical resection, confirming a diagnosis of adenocarcinoma. Conclusions For solitary pulmonary cystic airspaces (especially solitary multicystic lung lesions), it is important to properly recognise their imaging features. Due to the possibility of malignancies, timely surgery is an effective treatment strategy for early diagnosis.